Alternaria brown spot resistant citrus hybrid identification by means of fAFLP and pathogenicity tests - Chagas, Edvan Alves; Cazetta, Jairo Osvaldo; Lemos, Eliana Gertrudes Macedo; Pasqual, Moacir; Goes, Antonio; Ramos, Jose Darlan; Pio, Rafael; Barbosa, Wilson; Mendonça, Vander; Ambrosio, Luis Alberto (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to identify hybrids obtained from controlled crossings between 'Folha Murcha' x 'Ponkan', and to check their resistance to Alternaria alternata f. sp. citri. The seedlings were obtained by in vitro embryo culture. The fAFLP marker technique was used to identify the hybrids, then laboratory pathogenicity test of the hybrids was accomplished with Alternaria alternata f. sp. citri isolates. The pairs of primers EcoRI AAG – Msel CAG and EcoRI ACC – Msel CAA were the most efficient for hybrids identification, and distinguished 48.5% of hybrids. Hybrids F64, F108, F111, F113, F131 and F139 showed potential resistance to the Alternaria alternata f. sp. citri.